If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(5t + -4) + 6 = 40 + -1t Reorder the terms: 2(-4 + 5t) + 6 = 40 + -1t (-4 * 2 + 5t * 2) + 6 = 40 + -1t (-8 + 10t) + 6 = 40 + -1t Reorder the terms: -8 + 6 + 10t = 40 + -1t Combine like terms: -8 + 6 = -2 -2 + 10t = 40 + -1t Solving -2 + 10t = 40 + -1t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add 't' to each side of the equation. -2 + 10t + t = 40 + -1t + t Combine like terms: 10t + t = 11t -2 + 11t = 40 + -1t + t Combine like terms: -1t + t = 0 -2 + 11t = 40 + 0 -2 + 11t = 40 Add '2' to each side of the equation. -2 + 2 + 11t = 40 + 2 Combine like terms: -2 + 2 = 0 0 + 11t = 40 + 2 11t = 40 + 2 Combine like terms: 40 + 2 = 42 11t = 42 Divide each side by '11'. t = 3.818181818 Simplifying t = 3.818181818
| 49.2=1.5h | | 2(4m+1)=3 | | 114/95=95/x | | 6.4=16y | | xx/7-3=4 | | (2x-7)3=10x-9 | | -43=x/16 | | x-1=6/x | | 6x^3+56=53x-x^2 | | 7=5/6b-8 | | Y^2+3y=x | | (6+4x)*(15x+25)=0 | | F(x)=4*logx | | 3485x^2-311107.5x-18855000=0 | | n/36=17/72 | | 7w+6-3w=6 | | 4(2b-5)=2b+10 | | X/5-7=2 | | 2.3=y+.9 | | 12c-48=84 | | 9x-5=3x+47 | | x(x+13)=40 | | (1+2i)*x+(3-5i)*y=1-3i | | -3=2-(-x/5) | | 14x^2-5x+1=0 | | -12+x=60 | | 7x^2-14x-5=0 | | -6/13f=-48 | | 2nw=a | | xy-bx-ay+ab=0 | | 7/x=35/15 | | 2/3=5/2g |